2021
DOI: 10.1016/j.asmr.2021.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Deprivation Adversely Impacts Resident Performance for Simulated Arthroscopy

Abstract: Purpose The purpose of the study was to assess the performance of residents in orthopaedics before and after a 24-hour shift on a shoulder arthroscopy simulator. The primary study endpoint was an overall performance score (OPS) generated by the simulator. Methods A prospective, comparative study of 120 simulator trials by 10 resident junior surgeons was performed in our university hospital’s simulation center between May and November 2018. To avoid memorization bias, al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…While many studies have found positive correlations between seniority and surgical outcomes [ 30 ], only a few evaluated the impact of seniority on learning outcomes [ 3 , 5 , 22 ]. For example, Baumann et al found that the level of seniority was strongly correlated with performance on diagnostic ankle arthroscopy in a cadaveric model and observed year‐to‐year increases in global operative skills rating scales, task‐specific checklists, and oral questionnaires [ 3 ]. Martin et al also reported similar findings in shoulder arthroscopic training, noting a 16‐s improvement in the time required to complete a standardised object localisation task for every additional year of seniority [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While many studies have found positive correlations between seniority and surgical outcomes [ 30 ], only a few evaluated the impact of seniority on learning outcomes [ 3 , 5 , 22 ]. For example, Baumann et al found that the level of seniority was strongly correlated with performance on diagnostic ankle arthroscopy in a cadaveric model and observed year‐to‐year increases in global operative skills rating scales, task‐specific checklists, and oral questionnaires [ 3 ]. Martin et al also reported similar findings in shoulder arthroscopic training, noting a 16‐s improvement in the time required to complete a standardised object localisation task for every additional year of seniority [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…In shoulder, knee and ankle arthroscopy, a positive correlation was found between training level (postgraduate year [PGY]) and performance [ 15 , 22 ]. Sleep deprivation, in contrast, negatively affects the outcome of simulator training for residents [ 3 ]. Interestingly, Henn et al found that simulation training in knee arthroscopy did not improve proficiency in wrist arthroscopy among residents, indicating that competence in arthroscopy was not transferrable between joints, and a joint‐specific arthroscopy training programme is needed [ 13 ].…”
Section: Introductionmentioning
confidence: 99%